Sphere-cone-polynomial special window with good aberration characteristic - 王超 张新 曲贺盟 王灵杰 王钰 (Chinese physics B, 2013)
Optical windows with external surfaces shaped to satisfy operational environment needs are known as special windows. A novel special window, a sphere-cone-polynomial （SCP） window, is proposed. The formulas of this window shape are given. An SCP MgF2 window with a fineness ratio of 1.33 is designed as an example. The field-of-regard （FOR） angle is ±75°. From the window system simulation results obtained with the calculated fluid dynamics （CFD） and optical design software, we find that compared to the conventional window forms, the SCP shape can not only introduce relatively less drag in the airflow, but also have the minimal effect on imaging. So the SCP window optical system can achieve a high image quality across a super wide FOR without adding extra aberration correctors. The tolerance analysis results show that the optical performance can be maintained with a reasonable fabricating tolerance to manufacturing errors.